Influence of Walking as Physiological Training to Improve Respiratory Parameters in the Elderly Population - Novotová, Klára; Pavlů, Dagmar; Dvořáčková, Dominika; Arnal-Gómez, Anna; Espí-López, Gemma Victoria (International journal of environmental research and public health, 2022)
Walking as physiological training is reported to be an effective activity in order to beneficially influence and slow the onset of aging in healthy elderly people. However, insufficient evidence exists on how walking influences lung function in seniors. In our study, we aim to evaluate the effect of different types of walking on lung function in healthy seniors. The PubMed, Web of Science, Scopus and EBSCO Essentials databases were searched, while the methodological quality was assessed by the RoB2 tool. A total of seven studies (RCTs) published between 2002-2022 that met the eligibility criteria were analysed in this review. All participants were older adults without any specific associated disease, aged 60 and above. The interventions included structured physical activity; a high/moderate exercise program; long-term regular walking; walking as a part of functional movement training; walking sideways, backward and forward as a part of aerobic training; fast walking; Stepper walking; walking on a treadmill combined with incentive spirometry; and Nordic walking. Overall, most of the mentioned types of walking led to improved lung function in healthy elderly subjects. However, the prescribed Stepper walking program did not improve lung function in healthy seniors.
Keywords: elderly; dýchací soustava; zátěžový test; lung function; FVC; FEV1; lidé; cvičení; spirometry; Exercise Therapy; Aged; Walking; Exercise Test; terapie cvičením; older adults; senioři; walking; Exercise; aerobic training; chůze; Respiratory System; Humans